Trophy Hunting: To Ban Or Not To Ban? Legal Pathways For Zimbabwe In The Aftermath Of Cecil The Lion - Makuyana, Precious G. (Journal of Sustainable Development Law and Policy, 2025)
This article examines the legal framework and tools for achieving sustainable trophy hunting in Zimbabwe. Trophy hunting is part of wildlife tourism, in which wealthy tourists visit Zimbabwe to hunt for a unique, iconic wildlife with desirable phenotypic characteristics at a very high cost. The trophy hunting system was developed to achieve the tripartite objectives of conserving wildlife; providing local communities with economic opportunities and income; and incentivizing local communities to support environmental conservation initiatives. This article, however, highlights the blurred lines between the purported sustainable trophy hunting and its unsustainable implementation which now resembles “legal poaching.” This dichotomy was heightened by the killing of Cecil the Lion, a tourism icon in Zimbabwe when it was not listed under the quota system for trophy hunting. The wellintentioned legal frameworks on sustainable trophy hunting in Zimbabwe are weakened by broad exceptions that render them toothless to achieve the intended tripartite sustainability objectives. As demonstrated in this article, these tripartite objectives can be fulfilled by effective enforcement mechanisms that do not currently exist. Proposals are recommended to promote these objectives through reformation of the existing legal frameworks. The option to ban trophy hunting is examined through a socioeconomic analysis in Zimbabwe to determine whether it would be possible to support a complete ban. Zimbabwe’s current socioeconomic realities confirm that banning trophy hunting would be unlikely as doing so would devastate the tripartite objectives. Undertaking effective and sustainable policies is the more effective path for Zimbabwe at this time.